Comparative analysis of win and loss factors in women's handball using international competition records - Park, J.; Chang, K.; Ahn, J.; Kim, J.; Lee, S. (International Journal of Applied Sports Sciences, 2021)
This study identifies factors affecting match results from major international competitions in women's handball in the last four years. The 12 countries that participated for the 2020 Tokyo Olympics were included in the analysis, and a total of 281 matches from 4 major international competitions were analyzed. To identify factors affecting winning and losing, independent sample t-test and logistic regression analysis were conducted on the variables present in the official records. The findings present several factors that have positive and negative effects on match results. In the analysis of differences in win and loss factors, 6m goals success rate, 9m success rate, FB goals and shooting, AS, BS, and ST had positive effects on winning. Logistic regression analysis had 84.5% accuracy. 6m and Wing goal, 9m success rate, FB shooting, GK Wing save rate, and GK 9m save rate increased the probability of winning.